Corporate social responsibility and corporate financialization—Based on information effect and reputation insurance effect - Lei Lei; Di Zheng; XuDong Chen (PLoS ONE, 2022)
China has witnessed the trend of corporate financialization (CF) with some potential risks as the economy slows down its pace in the past decade. In this paper, we explore whether corporate social responsibility (CSR) could work as an information channel to restrain CF or as reputation insurance to promote CF. We find a significant positive relation between CSR and CF, especially for non-SOEs and enterprises with low ownership concentration and high CSR scores. It verifies that the reputation insurance effect by CSR outweighs the information effect and denies the opposite. The results prove robust in tests including sensitivity and endogeneity test. By expanding the scale and adding new aspects to the discussion about how CSR affects CF, this paper provides valuable empirical support to both theorists and practitioners.